2010
DOI: 10.4049/jimmunol.0904067
|View full text |Cite
|
Sign up to set email alerts
|

At Homeostasis Filarial Infections Have Expanded Adaptive T Regulatory but Not Classical Th2 Cells

Abstract: Despite the well-documented immune suppression associated with human helminth infections, studies characterizing the immune response at the single-cell level are scanty. We used multiparameter flow cytometry to characterize the type of effector (Th1, Th2, and Th17) and regulatory (natural T regulatory cells [nTregs] and adaptive Treg cells [aTreg/type 1 regulatory cells (Tr1s)]) CD4+ and CD8+ T cells in filaria-infected (Fil+) and -uninfected (Fil−) individuals at homeostasis (in the absence of stimulation). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 51 publications
4
110
1
3
Order By: Relevance
“…It is surprising that T1DM (an autoimmune disorder) and T2DM (a metabolic disorder), despite completely different underlying mechanisms for glucose intolerance, are modulated by LF infection. However, T1DM and T2DM are characterized by the presence of an intense inflammatory milieu, and filarial infections are known inducers of regulatory networks including regulatory T cells, 29,30 tolerogenic dendritic cells, 31 alternatively activated macrophages, 32 and anti-inflammatory cytokines. 33 Thus, it is not surprising that filarial infections exert such a profound effect on the prevalence of diabetes mellitus of autoimmune and metabolic origin.…”
Section: Discussionmentioning
confidence: 99%
“…It is surprising that T1DM (an autoimmune disorder) and T2DM (a metabolic disorder), despite completely different underlying mechanisms for glucose intolerance, are modulated by LF infection. However, T1DM and T2DM are characterized by the presence of an intense inflammatory milieu, and filarial infections are known inducers of regulatory networks including regulatory T cells, 29,30 tolerogenic dendritic cells, 31 alternatively activated macrophages, 32 and anti-inflammatory cytokines. 33 Thus, it is not surprising that filarial infections exert such a profound effect on the prevalence of diabetes mellitus of autoimmune and metabolic origin.…”
Section: Discussionmentioning
confidence: 99%
“…En este sentido, de una manera estricta no se puede generalizar sobre los efectos de los helmintos en la respuesta inmunológica a partir del hallazgo obtenido con una especie; sin embargo, hay poblaciones celulares que están ampliamente relacionadas con la infección por helmintos independientemente del tipo de parásito. Los linfocitos T reguladores (Treg) son un buen ejemplo de este tipo de blanco del sistema inmunológico que tienen los helmintos (10). Para otras poblaciones descritas de manera más reciente, tales como los linfocitos B reguladores, se necesitan más estudios en diferentes contextos de infección para conocer la universalidad del efecto inmunomodulador (11).…”
Section: Poblaciones Celularesunclassified
“…Es amplia la evidencia científica que respalda el efecto inductor de varias helmintiasis sobre los Treg (10,12). Además del fenotipo clásico de los Treg provenientes del timo (CD4 + CD25 + FOXP3 + ) se han descrito otras poblaciones circulantes productoras de IL-10 (Tr1) o TGF-β (10,13).…”
Section: Linfocitos T Reguladoresunclassified
“…77 It has been demonstrated that IgG can intercept allergen before it binds to IgE present on membranes of mast cells and basophils, 74 and that allergenIgG complexes can deactivate target cell by activation of the inhibitory Fc receptor (FcγRIIb), that in turn activates phosphatases in the molecular cross-linking regions of IgE shutting down FcεRI signaling. 78,79 A more unifying explanation suggests that IL-10, a primarily T-cell-derived cytokine commonly induced in chronic helminth infection, [80][81][82] may underlie the protection from SPT positivity. 11,83 Indeed, it is believed that the IL-10 modified Th2 response may be responsible for the parasite-antigen-specific tolerance imprinted on the host by helminth infection.…”
mentioning
confidence: 99%
“…11,83 Indeed, it is believed that the IL-10 modified Th2 response may be responsible for the parasite-antigen-specific tolerance imprinted on the host by helminth infection. 80,84,85 Parasite-induced IL-10 or other regulatory mechanisms-that can involve cell populations such as Tregs 81,86 and Bregs…”
mentioning
confidence: 99%